Faktor-Faktor Yang Mempengaruhi Kinerja Perusahaan Manufaktur Yang Terdaftar Di BEI - Olivia Trinita, Sofia Prima Dewi (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This research was conducted with the aim of obtaining empirical evidence regarding the factors that influence the performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). This study took data from annual reports for three periods, namely from 2015 to 2017 with total sampleas 65 companies. The sampling technique in this study was using purposive sampling and processed through program called Eviews version 9.5. The results obtained in this study indicate that capital employed efficiency has a positive effect on company performance, human capital efficiency has a negative effect on company performance, structural capital efficiency has no influence on company performance, capital structure has a negative influence on company performance, and firm size has an positive influence for company performance. Recommendation for the next studies is to add more independent variable such as audit committe, independent board of commissioners, and corporate social responsibility (CSR).